Policy announcement design - Cieślak, Anna,Malamud, Semyon,Schrimpf, Andreas (Swiss Finance Institute, 2020)
We study the general problem of information design for a policymaker—a central bank—that communicates its private information (the ``state
10.2139/ssrn.3504738
Keywords: Graue Literatur; Public Policy; Central Bank Announcements; Learning; Bayesian Persuasion; Information Design